Bad judgment : the myth of First Nations equality and judicial independence in Canada - Reilly, John, 1946- (Rocky Mountain Books, 2019)
The author, a judge, describes his legal problems after publishing his controversial book "Bad medicine", challenging the government's decision to subsequentially re-assign him.